Antioxidant potential and phenolic profile of blackberry anthocyanin extract followed by human gut microbiota fermentation. (June 2019) - Gowd, Vemana; Bao, Tao; Chen, Wei
Abstract: Beneficial properties attributed to the intake of blackberry fruit are associated with the presence of high content of anthocyanins. However, their low absorption and accumulation in the gut have generated the belief that gut metabolites of anthocyanins are probably reason for their protective effects. In this study, blackberry anthocyanins were prepared and subjected to in vitro human gut microbiota fermentation at different time intervals (0–48 h) to study their gut metabolites and antioxidant properties. The content of cyanidin-3- O -glucoside was found highest in blackberry and it degraded completely after 6 h fermentation. Gut metabolites of blackberry anthocyanins were found to improve the glucose consumption and glycogen content significantly in HepG2 cells. Furthermore, gut metabolites significantly ameliorated high glucose plus palmitic acid (HG + PA)-induced ROS, mitochondrial membrane collapse, and glutathione depletion in HepG2 cells. Overall, this study reveals that blackberry anthocyanins subjected to gut microbiota fermentation resulted in the formation of active metabolites with potential antioxidant activity against HG + PA-induced oxidative stress. Graphical abstract: Unlabelled Image Highlights: Cyanidin-3- O -glucoside (182.3 mg/g) was highest in blackberry anthocyanin extract Blackberry anthocyanin extract possessed strong cellular antioxidant activity Gut fermentation cannot alter antioxidant effect of blackberry anthocyanin extract Cyanidin-3- O -glucoside was completely degraded after 6 h gut fermentation Cyanidin-3- O -glucoside degradation resulted in formation of active gut metabolites